Availability and readiness of primary healthcare facilities for the management of non-communicable diseases in different districts of Punjab, Pakistan - Sadaf Rashid; Humaira Mahmood; Asma Asma Iftikhar; Nimrah komal; Zikria Butt; Hassan Mumtaz; Duha Shellah (Frontiers Media S.A., 2023)
IntroductionNon-communicable diseases (NCDs) and their effects are rising quickly. NCDs such as cardiovascular illnesses, diabetes, cancer, and chronic lung diseases cause 60% of global deaths; of which, 80% occur in developing countries. In established health systems, primary healthcare handles most of the NCD care.MethodologyThis is a mixed-method study conducted to analyze the health service availability and readiness toward NCDs using the SARA tool. It included 25 basic health units (BHUs) of Punjab, which were selected through random sampling. Quantitative data were collected using the SARA tools, while qualitative data were collected through in-depth interviews with healthcare providers working at the BHUs.ResultsThere was a problem of load shedding of both electricity and water in 52% of the BHUs, which leads to the poor availability of healthcare services. Only eight (32%) out of 25 BHUs provide the diagnosis or management of NCDs. The service availability was the highest for diabetes mellitus (72%), followed by cardiovascular disease (52%) and then chronic respiratory disease (40%). No services were available for cancer at the BHU level.ConclusionThis study raises issues and questions about the primary healthcare system in Punjab in two areas: first, the overall performance system, and second, the readiness of basic healthcare institutions to treat NCDs. The data show that there are many persisting primary healthcare (PHC) deficiencies. The study found a major training and resource deficit (guidelines and promotional materials). Therefore, it is important to include NCD prevention and control training in district training activities. NCDs are underrecognized in primary healthcare (PHC).